Konsep Rancang Bangun Smart Home Base Berbasis IOT untuk Skala Perumahan - Duta Catur Pamungkas Putra; Imani Rizkia Dawami; Muhammad Rofiul Haq; Achmad Daffa Danang Luthfiansyah; Alfan Mubarok; Dafit Ari Prasetyo (Indonesian Journal Publisher, 2023)
World energy demand continues to increase by 45% until 2030 based on projections of the International Energy Agency (IEA) with an average increase of 1.6% per year. About 80% of these energy needs supplied by fossil fuels. This increase occurred due to population growth, industrialization, lifestyle changes, and the use of increasingly complex technology. The household sector is one of the sectors that require energy to meet daily needs. Researchers conducted a study of research results related to rooftop Solar Power Plants, the use of thermoelectric as a producer of electrical energy, and the use of septic tanks for household gas with digesters that have been published in Indonesian-language journals and proceedings. The concept of a smart home base is implemented assuming a simple housing design, in this design than a technical calculation of the feasibility of a Smart Home Base is carried out which considers efficient methods in the development and provision of energy independently based on renewable energy for cost savings and supports government programs abaout Indonesia Ketahanan Energi 2030. Renewable energy applied to the smart home base concept utilizes Solar Power Plants which are hybrid with Thermoelectric Generators and biogas to replace of the LPG stove. Utilization of IoT-based technology to optimize energy savings at home. The housing concept is assumed with a simple housing design with a daily energy consumption of 5,507 Wh and 1,336 watts of power. The solar system used is 450 Wp for as many as 8 units of solar panels, 12 v 200 Ah battery capacity of as many as 8 units of batteries, and inverters with a power of 2000 Watts.